Review of Individual differences in language learning: A complex systems theory perspective; Authors: Carol Griffiths, Adem Soruç; Publisher: Palgrave Macmillan, 2020; ISBN: 978-3-030-52900-0; Pages: 220 - Ma, Mengyao; Gao, Xuesong (Andy) (Studies in Second Language Learning and Teaching, 2021)
Book Review: Individual differences in language learning: A complex systems theory perspective. Authors: Carol Griffiths, Adem Soruç. Publisher: Palgrave Macmillan, 2020. ISBN: 978-3-030-52900-0. Pages: 220.